Impact of fundamental factors on stock price: a case based approach on pharmaceutical companies listed with dhaka stock exchange - Haque, Samina; Faruquee, Murtaza (© 2013 International Journal of Business and Management Invention, 2016)
This article was published in International Journal of Business and Management Invention [© 2013 International Journal of Business and Management Invention] and the definite version is available at : http://www.ijbmi.org/papers/Vol(2)9/Version-1/G0291034041.pdf The article website is at: http://www.ijbmi.org/v2i9(version1).html